Characterization of a novel, papain‐inducible murine model of eosinophilic rhinosinusitis. Issue 4 (17th January 2018) - Tharakan, Anuj; Dobzanski, Alex; London, Nyall R.; Khalil, Syed M.; Surya, Nitya; Lane, Andrew P.; Ramanathan, Murugappan
Abstract : Background: Eosinophilic chronic rhinosinusitis (ECRS) is a disease characterized by eosinophilic inflammatory infiltrate and a local type 2 cytokine milieu. Current animal models fail to recapitulate many of the innate and adaptive immunologic hallmarks of the disease, thus hindering the development of effective therapeutics. In the present study, mice were exposed intranasally to the cysteine protease papain, which shares functional similarities with parasitic proteases and aeroallergens, to generate a rapidly inducible murine model of eosinophilic rhinosinusitis. Methods: C57BL/6 mice were intranasally instilled with 20 μg papain or heat‐inactivated papain (HP) on days 0–2 and days 7–10, and then euthanized on day 11. Nasal lavage fluid (NALF) was analyzed to quantify eosinophils and inflammatory cytokine secretion. Sinonasal tissue was sectioned and stained for goblet cells or homogenized to analyze cytokine levels. Serum samples were assayed for immunoglobulin E (IgE) by enzyme‐linked immunoassay. Sinonasal mucosal tissue was dissociated and analyzed by flow cytometry. Results: Compared with HP treatment, papain induced significant eosinophilia in NALF, goblet cell hyperplasia, innate and adaptive immune cell infiltration, type 2 cytokine production, and IgE responses. Flow cytometric analysis of sinonasal tissues revealed significant inflammatory cell infiltration and interleukin‐13–producing cell populations. Conclusion: In this study, we demonstrated that the cysteine protease papain induces allergic sinonasal eosinophilic rhinosinusitis and resembles T‐helper 2 cell inflammation and innate immune characteristics of ECRS. This model permits further study into the molecular mechanisms underlying ECRS pathology and provides a model system for the evaluation of potential pharmacologic interventions.